Optimising function and well-being in older adults: protocol for an integrated research programme in Aotearoa/New Zealand. - Lord S; Teh R; Gibson R; Smith M; Wrapson W; Thomson M; Rolleston A; Neville S; McBain L; Del Din S; Taylor L; Kayes N; et al. (BioMed Central Ltd, 2022)
Background Maintaining independence is of key importance to older people. Ways to enable health strategies, strengthen and support whanāu (family) at the community level are needed. The Ageing Well through Eating, Sleeping, Socialising and Mobility (AWESSOM) programme in Aotearoa/New Zealand (NZ) delivers five integrated studies across different ethnicities and ages to optimise well-being and to reverse the trajectory of functional decline and dependence associated with ageing. Methods Well-being, independence and the trajectory of dependence are constructs viewed differently according to ethnicity, age, and socio-cultural circumstance. For each AWESSoM study these constructs are defined and guide study development through collaboration with a wide range of stakeholders, and with reference to current evidence. The Compression of Functional Decline model (CFD) underpins aspects of the programme. Interventions vary to optimise engagement and include a co-developed whānau (family) centred initiative (Ngā Pou o Rongo), the use of a novel LifeCurve™App to support behavioural change, development of health and social initiatives to support Pacific elders, and the use of a comprehensive oral health and cognitive stimulation programme for cohorts in aged residential care. Running parallel to these interventions is analysis of large data sets from primary care providers and national health databases to understand complex multi-morbidities and identify those at risk of adverse outcomes. Themes or target areas of sleep, physical activity, oral health, and social connectedness complement social capital and community integration in a balanced programme involving older people across the ability spectrum. Discussion AWESSoM delivers a programme of bespoke yet integrated studies. Outcomes and process analysis from this research will inform about novel approaches to implement relevant, socio-cultural interventions to optimise well-being and health, and to reverse the trajectory of decline experienced with age. Trial registration The At-risk cohort study was registered by the Australian New Zealand Clinical Trials registry on 08/12/2021 (Registration number ACTRN 12621001679875).
Keywords: Co-morbidity; Dependency; Function; Mixed-methods design; Māori; Older adults; Pacific; Well-being; Aged; Aging; Australia; Cohort Studies; Exercise; Humans; New Zealand